Evaluating the Impact of the Nyala App on Depressive Symptoms and Suicidal Risk Among Adolescents - Estin Yuliastuti; Hery Siswanto; Adriesti Herdaetha; Tias Riski Oktaviana; Ilyas Fathur Rahman (Universitas Malahayati Lampung, 2025)
ABSTRACT Adolescent depression and suicide remain pressing global health concerns, particularly in low- and middle-income countries where access to mental health services is limited. Digital interventions have emerged as promising, accessible, and stigma-free alternatives for promoting youth mental health. This study aimed to evaluate the impact of the Nyala app on depressive symptoms and suicidal risk among adolescents. A posttest-only control group design was employed involving 40 adolescents aged 12–15 years from a private junior high school in Surakarta. Participants were divided into intervention (n = 20) and control (n = 20) groups. The intervention group used the Nyala app—which integrates psychoeducation, mood tracking, thought diary, and SOS crisis support—for two weeks. Depressive symptoms and suicidal risk were measured using the PHQ-9 and SBQ-R. Data were analyzed using the Mann–Whitney U test. The intervention group showed significantly lower mean scores for depressive symptoms (M = 2.35, SD = 2.64) compared to the control group (M = 8.50, SD = 7.02; p 0.001). Similarly, suicidal risk scores were lower in the intervention group (M = 4.00, SD = 0.00) than in the control group (M = 4.55, SD = 2.84; p 0.001). The Nyala app effectively reduced depressive symptoms and suicidal risk among adolescents. These findings support the integration of digital tools like Nyala into adolescent mental health services, especially in resource-limited and stigma-sensitive settings. Keywords: Adolescent Mental Health, Depression, Suicide Risk, Digital Intervention, Mobile Health, Nyala App.